PERAN MODERASI KOPING RELIGIUS POSITIF TERHADAP HUBUNGAN ANTARA PENGGUNAAN INTERNET BERMASALAH DENGAN KESEHATAN MENTAL - Rachman, Saeful; Jati, Alvira Andrea; Rafially, Shidqi; Shabrina, Arina (Psikologi UHAMKA, 2025)
The use of the internet is inseparable from everyday life. The ease of internet access makes many people, especially students, at risk of overusing the internet. However, excessive internet use can hurt mental health such as increased levels of stress, anxiety and depression. Previous studies have shown that positive religious coping can positively impact mental health. The purpose of this study was to determine the moderating role of positive religious coping on the relationship between internet overuse and mental health. This study used moderation analysis and tested three models. The sampling technique used was convenience sampling. The participants of this study were 147 undergraduate students at Universitas Muhammadiyah Bandung. This study used three measuring instruments, namely the modified GPIUS-2, religious coping scale and DASS-21 (Depression, Anxiety and Stress Scale-21). The results showed that there was no positive moderating role of religious coping on the relationship between problematic internet use and mental health in the student sample. In addition, the correlation results showed that problematic internet use was positively associated with depression, anxiety and stress. In the college student sample, positive religious coping was not significantly related to mental health. This study implies that there is a need to develop psychoeducation that aims to teach practical solutions so that individuals can use the internet wisely. Future research can consider other variables such as other types of coping.